Efficacy of aflibercept (EYLEA®) on inhibition of human VEGF in vitro - Schicht, Martin; Hesse, Karen; Schröder, Henrik; Naschberger, Elisabeth; Lamprecht, W.; Garreis, Fabian; Paulsen, Friedrich; Bräuer, Lars (Annals of Anatomy-Anatomischer Anzeiger, 2017)
Pathological formation of blood vessels plays a key role in the growth and metastasis of tumors and also in several serious ophthalmological diseases such as wet age-related macular degeneration (AMD) or diabetic retinopathy. In AMD treatment, aflibercept (tradename EYLEA®) is used to deactivate the underlying pathological neovascularisation. Aflibercept is a recombinant fusion protein which binds to vascular endothelial growth factor (VEGF) receptors, thereby inhibiting VEGF pathway activation. VEGF is one of the most important angiogenesis factors.This analysis investigates lasting efficacy of aflibercept in vitro for later application as therapeutic agent against macular degeneration (AMD).VEGF-ELISA assays were performed to investigate binding affinities at different aflibercept concentrations. The impact of VEGF on the proliferation of human umbilical vein endothelial cells (HUVEC) was investigated using proliferation assays. Moreover, time-dependent kinetic studies were performed to analyze different aflibercept storage durations with regard to its inhibitory capabilities on human VEGF.Our results reveal that aflibercept significantly lowers the amount of unbound VEGF as well as the proliferation rate of HUVEC. Moreover, in contrast to specifications given by the manufacturer, aflibercept retains its full inhibitory effect up to at least 120h after transference from the original vial into the injection syringe.
EVALuna2:15305
Keywords: Aflibercept; VEGF; VEGF-trap; EYLEA®; HUVEC